Case Report: Complex Congenital Brain Anomaly in a BBxHF Calf–Clinical Signs, Magnetic Resonance Imaging, and Pathological Findings - Veenema, Neeltje J.; Santifort, Koen M.; Kuijpers, Nienke W.; Seijger, Anne; Hut, Peter R. (Frontiers in Veterinary Science, 2021)
This case report describes the clinical signs, magnetic resonance imaging findings and associated (histo)pathological findings in a crossbred Belgian Blue calf with congenital complex brain anomaly. The calf was presented with non-progressive signs (including cerebellar ataxia) since birth suggestive of a multifocal intracranial lesion. A congenital anomaly was suspected and after serology and cerebrospinal fluid analysis, a magnetic resonance imaging study was performed. The following (suspected) abnormalities were identified: severe hydrocephalus, porencephaly, corpus callosum agenesis and increased fluid signal between the folia of the cerebellum. Post-mortem examination reflected the findings with MRI. The origin for these malformations could not be identified. There was no evidence for a causative infectious agent. Corpus callosum agenesis has been reported in bovines before and has been linked to bovine viral diarrhea virus (BVDV) infections, as have several other central nervous system anomalies in this species. In this case, BVDV was deemed an unlikely causative agent based on serology test results and lack of typical histopathological signs. The etiology of the congenital anomaly present in this bovine calf remains unknown.